Chromogenic bacterial staining of teeth: a scoping review - Mathangi Kumar; Medhini Madi; Ravindranath Vineetha; Divya Gopinath (BMC Oral Health)
Abstract Background The purpose of this scoping review is to understand the etiological, clinical characteristics and treatment of chromogenic staining of teeth and the various management strategies reported in literature. This SR was performed in accordance with the PRISMA 2022 guidelines and was registered in the PROSPERO database (CRD42024565446). Methods A systematic electronic search on databases like Scopus, Medline, EMBASE, CINAHL, ProQuest and Web of Science from inception to July 2024 was performed. Two independent reviewers ran the search strategy in the mentioned databases. Results A total of 989 articles were obtained from various databases. 21 were included for data extraction of which 2 were case reports, 1 was case series and 18 were research articles. The prevalence of staining due to chromogenic bacteria reported from the included studies ranged from 3.1 to 18.5%. All these studies reported on the typical black color of staining of teeth. Conclusion This scoping review reveals sparsity in existing literature regarding the etiological, clinical characteristics and management of chromogenic staining of teeth. Though the role of peculiar oral microbiota is well established, evidence regarding the management strategies to combat these recalcitrant staining remains a strong research question.